Fetal lung interstitial tumor: The first Japanese case report and a comparison with fetal lung tissue and congenital cystic adenomatoid malformation/congenital pulmonary airway malformation type 3. (18th October 2013) - Yoshida, Mariko; Tanaka, Mio; Gomi, Kiyoshi; Iwanaka, Tadashi; Dehner, Louis P.; Tanaka, Yukichi
Abstract : Fetal lung interstitial tumor, a newly recognized lung lesion in infants, was first reported in 2010. Here, we report the first Japanese case of fetal lung interstitial tumor which was originally diagnosed as atypical congenital cystic adenomatoid malformation/congenital pulmonary airway malformation type 3. A 7‐day‐old girl was referred to our hospital with respiratory distress and a left lung mass and she subsequently underwent left lower lobectomy. The specimen showed a 5 cm solid mass with a fibrous capsule. Histological examination revealed immature airspaces and interstitium, containing bronchioles and cartilage. The epithelial and interstitial cells contained abundant glycogen granules. Immunohistochemistry showed nuclear/cytoplasmic expression of β‐catenin in the epithelial and interstitial cells. β‐catenin gene mutations and trisomy 8 were not detected, so a neoplastic origin could not be confirmed. The histological findings were partly consistent with normal fetal lung at the canalicular stage, pulmonary interstitial glycogenosis, and congenital cystic adenomatoid malformation/congenital pulmonary airway malformation type 3. In this report, we compare the above conditions and discuss the pathogenesis of fetal lung interstitial tumor.